'Last of the buffalo': bison extermination, early conservation, and visual records of settler colonization in the North American west. (2nd January 2020) - Taschereau Mamers, Danielle
ABSTRACT: Following their rapid extermination from North America in the nineteenth century, bison became an icon of the early conservation movement. The acquisition of the last free-ranging bison herd by the Canadian government in 1907 was celebrated as a critical measure in preventing extinction. This article examines a photographic souvenir booklet that documents the round up, 'Last of the Buffalo'. The booklet's celebratory narrative of early-twentieth century conservation is also a visual record of settler colonization. Beginning with a history of Canada's acquisition of the Pablo herd, this article examines how the round up of these animals converged with processes of enclosure, dispossession, and the disavowal of Indigenous sovereignty. Turning to a visual analysis of the 'Last of the Buffalo', this paper then identifies settler logics and framing at work in the material and symbolic transformation of bison into objects of consumption. As an instance of settler colonial ways of seeing, the photographs establish a visual account of conservation that naturalizes the dispossession of Indigenous land and life. Finally, the article turns to the work of Tasha Hubbard (nêhiyaw), Zoe Todd (Métis), and Leroy Little Bear (Kainai), to indicate possible counter-readings of the photographs, as documents of a radical shift in a world of shared human-buffalo relations.